Produksi dan Pemasaran Kopi-Pro dengan Penambahan Probiotik Asli Indonesia Sebagai Alternatif Minuman Sehat - Feliatra, Feli; Azuga, Nabila A.; Adelina, Adelina; Simarmata, Asnika H.; Hendris, Sefni; Oktavian, Rizki (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
Coffee consumption continues to rise in step with growing interest in functional beverages. KOPI-PRO is a coffee product containing protein produced through fermentation by probiotic microorganisms and has undergone challenge tests against pathogenic bacteria such as Pseudomonas sp., Aeromonas sp., and Vibrio alginolyticus. This community engagement program aims to foster entrepreneurship among the academic community of the University of Riau by developing probiotic coffee (KOPI-PRO) as both a healthy product innovation and a pilot for a sustainable business strategy. Activities included outreach and production training, limited market trials, a consumer satisfaction survey (n = 39), and a business feasibility assessment. Results showed that four students chose to continue the KOPI-PRO venture; consumer ratings of taste, texture, and aroma ranged from “like” to “strongly like,” with the most favored variants including Orange Latte, Original, and Palm Sugar Latte. Financially, the venture was feasible (R/C > 1) with an estimated payback period of about four months. This program demonstrates that a simple, measurable, biotechnology-based service model is effective in cultivating students’ entrepreneurial interest and is readily replicable in campus and community settings.